Semiconductor safety handbook safety and health in the semiconductor industry - Bolmen, Richard A. (Semiconductor safety series., 1998)
The purpose of the Semiconductor Safety Handbook is to provide a current, single source reference for many of the primary semiconductor EH & S technologies and disciplines. To this end, the contributors have assembled a comprehensive text written by some of the leading experts in EH & S in the semiconductor industry.